2016
DOI: 10.1002/j.0022-0337.2016.80.2.tb06072.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Academic Performance in Dental Students: The Role of Coping Strategies and Examination‐Related Self‐Efficacy

Abstract: Academic stress negatively affects students' performance. However, little is known of the processes that may be involved in this association. This study aimed to analyze how other variables such as coping strategies and exam-related self-efficacy could be related to academic stress and performance for dental students. An online survey, including measures of coping strategies, perceived stress, exam-related self-efficacy, and academic performance, was completed by undergraduate dental students in Madrid, Spain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
116
2
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(152 citation statements)
references
References 25 publications
(26 reference statements)
11
116
2
17
Order By: Relevance
“…However, this study finds that stress has no significant impact on academic performance, and only anxiety presents a weak predictive effect on academic performance among all negative emotions, which is quite different from previous studies and verifies H2. Past research has shown that high levels of anxiety and depression have a negative effect on students' academic performance, since they can affect memory as well as concentration [12,13,17], and students with more academic stress are more likely to perform poorly on exams [14]. Achievement goals and academic self-efficacy are not controlled in these studies, so the conclusions may be biased, and negative emotions may not directly affect academic performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this study finds that stress has no significant impact on academic performance, and only anxiety presents a weak predictive effect on academic performance among all negative emotions, which is quite different from previous studies and verifies H2. Past research has shown that high levels of anxiety and depression have a negative effect on students' academic performance, since they can affect memory as well as concentration [12,13,17], and students with more academic stress are more likely to perform poorly on exams [14]. Achievement goals and academic self-efficacy are not controlled in these studies, so the conclusions may be biased, and negative emotions may not directly affect academic performance.…”
Section: Discussionmentioning
confidence: 95%
“…Research has shown support for the relationship between negative emotions and academic performance [11]. High levels of anxiety and depression have been found to have a negative effect on students' academic performance [12,13], and students with more academic stress are also more likely to perform poorly in academic achievement [14]. Aronen et al reported that anxiety and depression can affect memory as well as concentration, which leads to poor academic performance [15].…”
Section: Negative Emotionsmentioning
confidence: 99%
“…We have conducted the preliminary analysis to ensure that the assumptions of linearity, independence, normality and homoscedasticity are not violated. As suggested by Crego et al (2016), all the variables are standardized (i.e., converted to Z-score) in order to avoid the problem of multi-collinearity prior to conducting the path analysis.…”
Section: Methodsmentioning
confidence: 99%
“…With the development in technology and the introduction of human stress monitoring devices (such as small watches), stress can be directly recorded by the survey interviewer. Moreover, surveys might lead to memory error, order effects and social desirability bias (Crego et al, 2016). However, we conducted the survey very close to their term exam, responses with respect to perceived stress score will be most likely accurate.…”
Section: Journal Of Sociological Researchmentioning
confidence: 99%
“…Nghiên cứu của Renk và Eskola (2007) (Coiro và c.s., 2017), ít lo âu hơn (Renk & Eskola, 2007), có trạng thái lành mạnh về tâm lý cao hơn (Park & Adler, 2003), mức độ hài lòng với cuộc sống cao hơn (Deniz, 2006), chịu ít tác động tiêu cực đối với thể chất hơn (Coiro và c.s., 2017;Dunkley, Blankstein, Halsall, Williams, & Winkworth, 2000;Park & Adler, 2003;Sasaki & Yamasaki, 2007), khả năng thích ứng với môi trường học tập hay tình huống stress tốt hơn (Leong và c.s., 1997;Shields, 2001), có động lực và kết quả học tập cao hơn (M. Cohen, Ben-Zur, & Rosenfeld, 2008;Shields, 2001;Struthers và c.s., 2000). Ngoài ra, chiến lược ứng phó tìm kiếm chỗ dựa xã hội về mặt cảm xúc, suy nghĩ tích cực, hay thay đổi nhận thức cũng được sinh viên đánh giá là có hiệu quả (Brougham và c.s., 2009;Dunkley và c.s., 2000;Kirkland, 1998) và đem lại những hệ quả tích cực như cảm giác hài lòng với cuộc sống (Deniz, 2006), khả năng phục hồi cao hơn (Malhotra & Chebiyyam, 2017), mức độ stress (Crego, Carrillo-Diaz, Armfield, & Romero, 2016), lo âu và trầm cảm (Siu & Chang, 2011) thấp hơn.…”
Section: Tổng Quan Nghiên Cứu Về ứNg Phó Với Stress Trong Học Tậpunclassified